Model Pembelajaran Kolaboratif Pada Program Tahfizh Al-Qur’an Untuk Meningkatkan Motivasi Menghafal Al-Qur’an Santri Al-Wafi Islamic Boarding School Depok - Alfian Zulfikar; Sastradiharja, Junaedi; Farizal MS (STAI Yogyakarta, 2024)
This research aims to describe and discover the 'Collaborative Learning Model in the Tahfidz Al-Qur’an program to enhance the motivation of students in memorizing the Al-Qur’an at Ma’had Al-Wafi Islamic Boarding School.' The method used in this research is a survey method with techniques including interviews, observations, and document studies. The sources of data or informants in this research are the head of tahfidz, Al-Qur’an teachers, and students at Ma’had Al-Wafi IBS. The results of this research are as follows: First, the implementation strategy of collaborative learning in the tahfizh program at Alwafi IBS is carried out through several stages: 1) Learning needs analysis, 2) Learning group mapping, 3) Setting learning objectives, 4) Establishing learning targets, 5) Setting learning schedules, 6) Selecting learning methods and techniques, 7) Learning evaluation. Second, the steps to enhance the motivation of students in memorizing the Qur'an at Ma’had Al-Wafi IBS through the following stages: 1) Preparing students before memorizing the Qur'an, 2) Making the learning process enjoyable, 3) Creating a supportive environment, 4) Implementing rewards and punishments, 5) Collaboration among teachers in motivating students, 6) Collaborating with parents in motivating students. Third, the conclusion is that the collaborative learning model in the tahfizh program of the Qur'an at Ma’had Al-Wafi IBS has made a significant contribution to increasing students' motivation to memorize, as evidenced by the following indicators: 1) Reducing students' boredom and laziness in memorizing the Qur'an, 2) Non-monotonous learning, so students can memorize happily, which impacts the quality of their memorization, 3) Students' progress in memorization became more intensive and effective, as seen in their daily memorization activities.